10Be/9Be Ratios Reflect Antarctic Ice Sheet Freshwater Discharge During Pliocene Warming. Issue 9 (3rd September 2018) - Valletta, Rachel D.; Willenbring, Jane K.; Passchier, Sandra; Elmi, Chiara
Abstract: Along glaciated margins, ratios of meteoric cosmogenic beryllium‐10, 10 Be, normalized to its stable isotope, 9 Be, reflect an environmental signal, driven ultimately by climatic change. We explore the application of this isotopic pair as a proxy for East Antarctic Ice Sheet dynamics. We analyze 10 Be/ 9 Be in middle Pliocene glaciomarine sediments offshore the Wilkes Land Region (Integrated Ocean Drilling Program (IODP) Site U1361A) and examine our new record alongside existing biochemical/geochemical records (Ba/Al, opal %wt, εNd, and 87 Sr/ 86 Sr). 10 Be/ 9 Be ratios reach local maxima during pulsed, mild warming events and are strongly correlated with existing records that indicate concurrent ice sheet retraction and increased bioproductivity. We suggest climate change as the primary driver of the 10 Be/ 9 Be record near glaciated margins, whereby increased warming drives ice sheet retraction, discharging freshwaters and diluting the open ocean 10 Be/ 9 Be signal recorded in authigenic minerals. Plain Language Summary: If the entire Antarctic Ice Sheet collapsed, it would raise global sea level by about 60 m (200 feet). How sensitive is the ice sheet to warming temperatures? Should we expect extreme sea level rise by the middle to late century, when global average temperatures could warm by about 2 °C (3.6 °F) or more? To answer these questions, earth scientists design numerical models to simulate ice sheet behavior and improve those models using physical evidence. High‐quality physical evidence is found in the marine sedimentary record deposited in the past under analogous warm conditions, such as during the Pliocene period (2.6–5.3 million years ago). The elemental and isotopic composition of these marine sediments gives clues as to how the ice sheet has reacted to warming temperatures. One such isotope is beryllium‐10 ( 10 Be), which, in specific environments, fluctuates in tandem with glacial‐interglacial transitions. As additional marine sediment records identify specific mechanisms of ice mass loss at work, we begin to strengthen predictions of sea level rise from numerical simulations. Key Points: 10 Be/ 9 Be in Pliocene‐age glaciomarine sediments offshore the Wilkes Subglacial Basin (WSB) reflect oscillations in the East Antarctic Ice Sheet (EAIS) Freshwater discharge via basal ice melt can account for the observed 10 Be inventory entering Adélie Land Bottom Water (ALBW) Variation in the 10 Be/ 9 Be ratio is used to estimate freshwater discharge and deep water dilution